The Integration Model of Malay Jambi Customary Law Values into the National Legal System for the Resolution of Customary Land Compensation Disputes - Suhermi Suhermi; Herlina Manik; Umar Hasan; Diana Amir (JURNAL AKTA, 2025)
Agrarian conflicts in Jambi Province, particularly those related to compensation for customary land (tanah ulayat), reveal the weak integration between customary law and positive law in protecting indigenous peoples’ rights. This study aims to analyze the implementation of compensation for customary land in Jambi and formulate a model of integrating Malay Jambi customary law values into the national legal system. The research employed a normative juridical method with conceptual and evaluative approaches, supported by secondary empirical data from civil society organizations such as WALHI, BRWA, and AMAN. The findings indicate that compensation practices in Jambi emphasize individual cash payments, disregarding the communal nature and spiritual dimensions of customary land. This situation is often exacerbated by the criminalization of indigenous communities in disputes with corporations, further weakening their bargaining position in conflict resolution. As a solution, this study proposes the HARMONI-ULAYAT Model, a framework for integrating the spiritual, social, participatory, and collective sovereignty values of Malay Jambi customary law into positive law. This model can take the form of local policies, administrative regulations, or hybrid tribunals to institutionalize adat-based conflict resolution. This article contributes to the development of agrarian and customary law studies and provides a reference for more responsive policies toward substantive justice.